Thionine-Bromate as a New Reaction System for Kinetic Spectrophotometric Determination of Hydrazine in Cooling Tower Water Samples - Masoud Reza Shishehbore; Ali Sheibani; Masoumeh Eslami (Journal of Chemistry)
A simple, selective, and inexpensive kinetic method was developed for the determination of hydrazine based on its inhibitory effect on the thionine-bromate system in sulfuric acid media. The reaction was monitored spectrophotometrically at 601 nm by a fixed time method. The effect of different parameters such as concentration of reactants, ionic strength, temperature, and time on the rate of reaction was investigated, and the optimum conditions were obtained. Under optimum conditions, the calibration curve was linear in the concentration range from 0.8–23.0 μg mL−1 of hydrazine, and the detection limit of the method was 0.22 μg mL−1. The relative standard deviation for five replicate determinations of 1.0 μg mL−1 of hydrazine was 0.74%. The potential of interfering effect of foreign species on the hydrazine determination was studied. The proposed method was successfully applied for the determination of hydrazine in different water samples.